2005
DOI: 10.1136/thx.2004.034280
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal of fluticasone propionate from combined salmeterol/fluticasone treatment in patients with COPD causes immediate and sustained disease deterioration: a randomised controlled trial

Abstract: Background: Guidelines recommend inhaled corticosteroids (ICS) as maintenance treatment for patients with chronic obstructive pulmonary disease (COPD) with a post-bronchodilator forced expiratory volume in 1 second (FEV 1 ) ,50% predicted and frequent exacerbations, although they have only a small preventive effect on the accelerated decline in lung function. Combined treatment with ICS and long acting b 2 agonists (LABA) may provide benefit to the stability of COPD, but it is unknown if withdrawal of ICS will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(93 citation statements)
references
References 28 publications
5
86
0
2
Order By: Relevance
“…81 Studies examining the effect of ICS withdrawal reported some deterioration in disease control. [82][83][84][85] However, a recent meta-analysis highlighted methodological flaws in evaluable studies of ICS withdrawal in COPD and calculated that withdrawal of ICS resulted only in a small and insignificant increase in exacerbations. 86 Nevertheless, a preferable approach would be to ensure the correct treatment strategy from the outset, with the use of ICS reserved for patients in whom the benefit will outweigh the risk.…”
Section: Patients Already On Icsmentioning
confidence: 99%
“…81 Studies examining the effect of ICS withdrawal reported some deterioration in disease control. [82][83][84][85] However, a recent meta-analysis highlighted methodological flaws in evaluable studies of ICS withdrawal in COPD and calculated that withdrawal of ICS resulted only in a small and insignificant increase in exacerbations. 86 Nevertheless, a preferable approach would be to ensure the correct treatment strategy from the outset, with the use of ICS reserved for patients in whom the benefit will outweigh the risk.…”
Section: Patients Already On Icsmentioning
confidence: 99%
“…If hospitalization was required, at the discretion of the clinician, exacerbation was considered severe. We included only moderate and severe exacerbations in the exacerbation group of COPD, as in other studies [15,16]. Spirometry (Elite-DX or CPFS; Medgraphics, Saint Paul, Minn., USA) was performed according to the American Thoracic Society guidelines [17].…”
Section: Methodsmentioning
confidence: 99%
“…Data were collected from 295 COPD patients participating in the COSMIC (COPD and Seretide: A multi-center intervention and characterization) study (post-bronchodilator FEV 1 between 30% and 80% predicted; FEV 1 /FVC ratio < 70% predicted) at 39 outpatient centers in the Netherlands [16]. The central ethical committee in the Netherlands and the local medical ethics committees of the participating centers approved the study.…”
Section: Methodsmentioning
confidence: 99%